Diabetes and two kinds of primary tumors in a patient with thalassemia: a case report and literature review - Yu, Xiaoyan; Peng, Yi; Nie, Tingting; Sun, Wenjia; Zhou, Yajuan (Frontiers in Oncology, 2023)
Background: Thalassemia is a group of common genetic hematologic disorder, characterized by deficient synthesis of hemoglobin chain. Due to effective blood transfusion and optimizing chelate therapy, survival of thalassemia patients and overall quality of life has noticeably improved in the past few decades. As a consequence, the longer lifespan has led to the manifestation of several concomitant morbidities, including heart disease, infection, cirrhosis, endocrine abnormalities, various malignancies and so on. In this context, the probability and updated literature about some malignancy case in patients with thalassemic build the new scenarios for the next few years. We describe first report of a thalassemic patient developing diabetes and head and neck cancer, and try to summarize the possible predisposing factors and mechanisms behind their phenomenon.The current case report describes a 50-year-old Asian male who was diagnosed with thalassemia since childhood. In early 2017, he was diagnosed with diabetes, and then started on the insulin hypoglycemic treatment. The patient was diagnosed with primary nonkeratinizing undifferentiated carcinoma of the nasopharynx in late February 2013. A biopsy of the left tongue demonstrated squamous cell carcinoma (SCC) at the end of March 2019.We report the first case of a thalassemic patient developing diabetes and head and neck squamous cell carcinoma, and discuss the internal possibility of a link between the three diseases. This special case is intended to alert physicians of the possibility of endocrinopathy and malignant tumor in thalassemia patients.